Aktivitas Ekstrak Metanol Daun Akasia (Acacia mangium Wild) Terhadap Perkecambahan Dan Pertumbuhan Maman Ungu (Cleome rutidospermaeD.C) Dan Rumput Grinting (Cynodon dactylon L. Pers) - Diah Wulandari Rousdy, Sumi Riza linda (Universitas Tanjungpura, 2018)
Acacia (Acacia mangium Wild.) have alelokimia compound that can suppress the growth of the plants that it can be used as bioherbicide. This aimto study determined the concentration of the methanol extract of leaf of acacia capable of inhibit the germination and growth of weed, purple maman (Cleome rutidospermae DC.) and grass grinting(Cynodon dactylon L.). This study use a completely randomized design (CRD) with five replication and five treatment consist of control, concentrationmethanolextract0.2; 0.4; 0.6 and 0.8 g mlË‰1.Resultshowed that the methanol extract of leafacacia with a concentration of 0.4 g mlË‰1able to inhibit germinationpurple maman and grass grinting. Concentration of 0.2 g mlË‰1extract acacia can inhibit the growth of plant height, root length, and a decrease in wet weight and dry weight in weed purple maman andgrass grinting